Electromechanical response of delaminating polymer thin films on rough elastomeric substrate. (December 2017) - Mehdi, Syed Murtuza; Akhtar, Maaz; Qamar, Sayyad Zahid
Conductive polymer poly(3, 4-ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT/PSS) is being considered as an alternate material for metallic thin-film conductors in numerous biomedical sensing applications. This study investigates the electromechanical response of delaminating thin films of this conductive polymer (PEDOT/PSS) on a highly compliant elastomeric substrate called polydimethylsiloxane. The value of Young's modulus for the substrate was tuned to remain between 120 kPa and140 kPa, while its thickness was at a submillimeter level. The films were fabricated using a non-vacuum, scalable, and cost-effective method of rod coating. The films were intentionally fabricated in a way, so that when the tensile strain is applied, the films are only loaded through interfacial shear, which results in delamination of the films instead of cracking. The experiments indicate an onset of delamination at an average value of 13.3% strain with continuous increase in resistance up to an average of 26% strain for the as-fabricated laminate. The study presents simple mathematical models relating the variation of electrical resistance with the applied strain which can be of potential use in predicting the response of such a polymer–elastomer laminate in areas like flexible and stretchable electronic sensing.